Improved deep learning architecture for skin cancer classification - Owida, Hamza Abu; Alshdaifat, Nawaf; Almaghthawi, Ahmed; Abuowaida, Suhaila; Aburomman, Ahmad; Al-Momani, Adai; Arabiat, Mohammad; Chan, Huah Yong (Institute of Advanced Engineering and Science, 2024)
A leading cause of mortality globally, skin cancer is deadly. Early skin cancer diagnosis reduces mortality. Visual inspection is the main skin cancer diagnosis tool; however, it is imprecise. Researchers propose deep-learning techniques to assist physicians identify skin tumors fast and correctly. Deep convolutional neural networks (CNNs) can identify distinct objects in complex tasks. We train a CNN on photos with merely pixels and illness labels to classify skin lesions. We train on HAM-10000 using a CNN. On the HAM10000 dataset, the suggested model scored 95.23% efficiency, 95.30% sensitivity, and 95.91% specificity.